2021
DOI: 10.1038/s41598-021-87112-2
|View full text |Cite
|
Sign up to set email alerts
|

Different Zn loading in Urea–Formaldehyde influences the N controlled release by structure modification

Abstract: Nitrogen fertilization has been a critical factor for high crop productivity, where urea is currently the most used N source due to its high concentration and affordability. Nevertheless, urea fast solubilization leads to frequent losses and lower agronomic efficiency. The modification of urea structure by condensation with formaldehyde has been proposed to improve nutrient uptake by plants and to reduce environmental losses. Herein we show that the co-formulation with Zn strongly modifies the N release (in la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
(50 reference statements)
2
14
0
Order By: Relevance
“…The release pattern of coated urea is directly proportional to the microbial activity in soil (Gil-Ortiz et al, 2020). Soil microbes cause complete urea breakdown, allowing plants to absorb nitrogen, reducing nitrogen volatilization, and increasing zinc release from zinc-coated urea (Giroto et al, 2021). Bacteria convert nitrogen in the compound to nitrate, lowering soil pH and diminishing soil microbial diversity, which has a detrimental influence on the coated urea release pattern with zinc nanoparticles (Sadiq et al, 2021).…”
Section: E Ect Of Microbial Activity On Availability Of Coated Ureamentioning
confidence: 99%
See 1 more Smart Citation
“…The release pattern of coated urea is directly proportional to the microbial activity in soil (Gil-Ortiz et al, 2020). Soil microbes cause complete urea breakdown, allowing plants to absorb nitrogen, reducing nitrogen volatilization, and increasing zinc release from zinc-coated urea (Giroto et al, 2021). Bacteria convert nitrogen in the compound to nitrate, lowering soil pH and diminishing soil microbial diversity, which has a detrimental influence on the coated urea release pattern with zinc nanoparticles (Sadiq et al, 2021).…”
Section: E Ect Of Microbial Activity On Availability Of Coated Ureamentioning
confidence: 99%
“…For instance, Muster et al (2011) reported that Zn uptake is greatly affected by high temperatures in humid environments. High humidity contributes to accelerating the release of nitrogen from Zn-coated urea by increasing the amount of water retained at the soil surface (Giroto et al, 2021). Humidity affects soil temperature and water potential, reducing the efficiency of Zn-coated urea in soil and making it easier to solubilize the urea granules by adding water through coatings (Sadiq et al, 2021).…”
Section: E Ect Of Relative Humidity On Availability Of Coated Ureamentioning
confidence: 99%
“…The use of urea:urea-formaldehyde polymers (UF polymers) as N fertilizers has been proven an excellent option to overcome urea losses, as this material can deliver nutrients at a controlled rate, avoiding fast hydrolysis in soil (Giroto et al, 2021;Giroto and Ribeiro, 2018;Guo et al, 2018;Xiang et al, 2018;Zhang et al, 2020). Although most studies addressed macronutrient management, there are strong indications that micronutrient deficiencies significantly limit crop productivity (Kihara et al, 2017;Vanlauwe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…5 Zn loading can also help in controlling the release of Nfertilizers via structural modifications. 6 Zn adsorption− desorption with favorable desorption kinetics can be achieved by using Zn-based engineered materials for controlled Zn release into soil by suppressing the Zn leaching loss after fertilizer application. In such a strategy, biopolymers such as cellulose, chitosan, and alginate were utilized to deliver ZnO nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the past, zeolite and bentonite were known as nutrient adsorbents with controlled release of plant nutrients by the understanding of the sorption in zeolite and bentonite by following the Langmuir and Freundlich isotherm in which case a higher adsorption of Zn caused a lower percentage of desorption as can be found in slow-release fertilizers for Zn . Zn loading can also help in controlling the release of N-fertilizers via structural modifications . Zn adsorption–desorption with favorable desorption kinetics can be achieved by using Zn-based engineered materials for controlled Zn release into soil by suppressing the Zn leaching loss after fertilizer application.…”
Section: Introductionmentioning
confidence: 99%